GDPR-driven Change Detection In Consent And Activity Metadata - O'Sullivan, Declan; PANDIT, HARSHVARDHAN JITENDRA; Lewis, David (My University, 2018)
This position paper explores changes concerning the relationship between consent and activities in context of the General Data Protection Regulation (GDPR). Detecting and recording such changes with their effects can provide assistance in demonstration and management of compliance. We present an approach for using metadata-driven change detection and representation towards supporting querying for GDPR compliance. We use P-Plan (an extension to PROV) for representing provenance of activities and ODRL for representing consent. We explore the presented approach by means of a use-case.
Managing the Evolution and Preservation of the Data Web ? MEPDaW 2018 at 15th International Extended Semantic Web Conference (ESWC 2018)
Keywords: GDPR; Data protection; Metadata; Change detection; Compliance; Digital Engagement; Knowledge and data engineering